2019
DOI: 10.1246/bcsj.20180353
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Hydrolytic DNA Cleavage by Dicopper(II) Complexes withp-Cresol-Derived Dinucleating Ligands at Slightly Acidic pH and Mechanistic Insights

Abstract: Four dicopper(II) complexes, [Cu2(µ-X)(bcmp)](ClO4)2 [X = OH (1a) and X = Cl (1b)], [Cu2(µ-OH)(Me4bcmp)](ClO4)2 (2), and [Cu2(bcc)](ClO4)3 (3), were synthesized with three p-cresol-derived ligands, 2,6-bis(1,4,7-triazacyclononylmethyl)-4-meth-ylphenol (Hbcmp), 2,6-bis(1,4,7-triaza-4,7-dimethylcyclonon-ylmethyl)-4-methylphenol (HMe4bcmp), and 2,6-bis(1,4,7,10-tetrazacyclododecylmethyl)-4-methylphenol (Hbcc) to study hydrolytic DNA cleavage. Crystal structures of 1a, 1b, 2, and 3 were determined by X-ray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Previously, we reported that a dicopper­(II) complex with p -cresol-derived methylene-tether ligand [Cu 2 (bcc)]­(ClO 4 ) 3 ( 1 ) and related complexes accelerate hydrolytic DNA cleavage at pH 5–6, but 1 did not accelerate the DNA cleavage with H 2 O 2 . In this study, we synthesized a new p -cresol-derived amide-tether ligand 2,6-bis­(1,4,7,10-tetraazacyclododecyl-1-carboxamide)- p -cresol (Hbcamide) and found that its dicopper­(II) complex [Cu 2 (μ-OH)­(bcamide)]­(ClO 4 ) 2 ( 2 ) largely accelerates the oxidative DNA cleavage by H 2 O 2 without reductants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that a dicopper­(II) complex with p -cresol-derived methylene-tether ligand [Cu 2 (bcc)]­(ClO 4 ) 3 ( 1 ) and related complexes accelerate hydrolytic DNA cleavage at pH 5–6, but 1 did not accelerate the DNA cleavage with H 2 O 2 . In this study, we synthesized a new p -cresol-derived amide-tether ligand 2,6-bis­(1,4,7,10-tetraazacyclododecyl-1-carboxamide)- p -cresol (Hbcamide) and found that its dicopper­(II) complex [Cu 2 (μ-OH)­(bcamide)]­(ClO 4 ) 2 ( 2 ) largely accelerates the oxidative DNA cleavage by H 2 O 2 without reductants.…”
mentioning
confidence: 99%
“…The methylene- and amide-tether ligands, Hbcc and Hbcamide, used in this study have two tetraazacyclododecane (cyclen) pendant groups tethered at 2,6-positions of p -cresol by −CH 2 – and −CO– groups, respectively (Scheme ). Hbcc and [Cu 2 (bcc)]­(ClO 4 ) 2 ( 1 ) were prepared as previously reported . Hbcamide and [Cu 2 (μ-OH)­(bcamide)]­(ClO 4 ) 2 ( 2 ) are new compounds, and the synthetic details are shown in the Supporting Information.…”
mentioning
confidence: 99%
“…The synthetic details and spectroscopic characterization of HL1, HL2, 1 , 2a , b , and 3 are given in the Experimental Section. HL3, HL4, 4 , and 5 were prepared according to the literature. , HL1 was prepared in almost quantitative yield from bis­(2-pyridylmethyl)­amine and 4-methylphenol-2,6-dicarboxylic acid via formation of acid chloride by treatment with thionyl chloride. In this reaction, potassium carbonate was used as the base, but the yield of HL1 drastically decreased when triethylamine was used as the base.…”
Section: Resultsmentioning
confidence: 99%
“…All ordinary reagents including N,N′ -dicyclohexylcarbodiimide (DCC), 4-dimethylaminopyridine (DMAP), 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), trifluoroacetic acid (TFA), N -(3-(dimethylamino)­propyl)- N′ -ethylcarbodiimide hydrochloride (EDC·HCl), and solvents were purchased and used as received unless otherwise noted. The dicopper complexes of HL3 and HL4, [Cu 2 (μ-OH)­(L3)]­(ClO 4 ) 2 ( 4 ) and [Cu 2 (μ-OH)­(L4)]­(ClO 4 ) 2 ( 5 ) respectively, were synthesized according to the literature. , pUC19 DNA was purchased from Nippon Gene Co., Ltd. 4-Methylphenol-2,6-dicarboxylic acid ( 6 ), 1-amino-8-azido-3,6-dioxaoctane ( 12 ), and complex 5 were prepared according to the literature. ,, Caution! Perchlorate salts are potentially explosive and should be handled with great caution .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation